THE EFFECT OF COMPLEMENTARY THERAPIES OF SLOW DEEP BREATHING AND LAVANDULA ESSENTIAL OIL FOR INCREASING FEMALE PRISONERS’ SELF-ESTEEM AT THE CORRECTIONAL FACILITY, CLASS IIB, YOGYAKARTA - Khadijah, Sitti; Palifiana, Dheska Arthyka (Jurnal Keperawatan Respati Yogyakarta, 2021)
Prisoners will undoubtedly experience major changes in the prison in terms of environment, roles, and activities during their detention. All these changes make them experience a decrease in self-esteem. Complementary therapy in the forms of slow deep breathing and essential oil of Lavandula can cause physical and psychological relaxation so that it is expected to affect the prisoners’ self-esteem. This study aimed to find out the effect of complementary therapies of slow deep breathing and Lavandula essential oil on female prisoners’ self-esteem. The type of this study was experimental research using a pre-post-test design and a two-group design. Samples in this study consisted of 41 respondents. Furthermore, the employed data analysis was the Wilcoxon test. The results in this study indicated that the majority of respondents were in the categories of early adulthood (65.9%), having secondary education level (48.8%), having been married (48.8%), and having a length of sentence of 1 – 5 years (61%). In the group given slow deep breathing therapy, respondents who had low self-esteem in the pre-test was 33.33%. However, in the post-test, they decreased to 5.56%. Meanwhile, its significance value (2-tailed) was 0.025 (p < 0.05). In the group given Lavandula essential oil therapy, respondents who had low self-esteem in the pre-test was 34.78%. However, in the post-test, they also decreased to 4.34%. Meanwhile, its significance value (2-tailed) was 0.008 (p < 0.05). It can be concluded that complementary therapies of slow deep breathing and Lavandula essential oil can increase female prisoners’ self-esteem.